Heroin- and Fentanyl-Induced Respiratory Depression in a Rat Plethysmography Model: Potency, Tolerance, and Sex Differences - Marchette, Renata C.N.; Carlson, Erika R.; Frye, Emma V.; Hastings, Lyndsay E.; Vendruscolo, Janaina C.M.; Mejias-Torres, Gustavo; Lewis, Stephen J.; Hampson, Aidan; Volkow, Nora D.; Vendruscolo, Leandro F.; Koob, George F. (The Journal of pharmacology and experimental therapeutics, 2023)
The opioid overdose death toll in the United States is an ongoing public health crisis. We characterized the magnitude and duration of respiratory depression, the leading cause of death in opioid overdose cases, induced by heroin or fentanyl and the development of tolerance in male and female rats. We used whole-body plethysmography to first establish dose-response curves by recording breathing for 60 minutes post-intravenous opioid injection. We then tested the development of respiratory tolerance to acute heroin or fentanyl over several weeks and to chronic fentanyl with acute fentanyl or heroin challenge. Heroin and fentanyl each provoked dose-dependent respiratory depression. Heroin caused prolonged (45–60 minute) respiratory depression in female and male rats, characterized by decreased frequency, tidal volume, and minute ventilation and increased inspiratory time and apneic pause. Fentanyl produced similar changes with a shorter duration (10–15 minutes). High-dose heroin or fentanyl produced robust respiratory depression that was slightly more severe in females and, when given intermittently (acute doses 2 to 3 weeks apart), did not lead to tolerance. In contrast, chronic fentanyl delivered with an osmotic minipump resulted in tolerance to acute fentanyl and heroin, characterized by a shorter duration of respiratory depression. This effect persisted during withdrawal in males only. Our model and experimental design will allow for investigation of the neurobiology of opioid-induced respiratory depression and for testing potential therapeutics to reverse respiratory depression or stimulate breathing. Fentanyl was more potent and had shorter duration in producing respiratory depression than heroin in both sexes, whereas female rats were more sensitive than males to heroin-induced respiratory depression. Tolerance/cross-tolerance develops in chronic fentanyl administration but is minimized with long interadministration intervals.